Childhood Arthritis and Rheumatology Research Alliance consensus clinical treatment plans for juvenile dermatomyositis with skin predominant disease. Issue 1 (December 2017) - Kim, Susan; Kahn, Philip; Robinson, Angela; Lang, Bianca; Shulman, Andrew; Oberle, Edward.; Schikler, Kenneth; Curran, Megan; Barillas-Arias, Lilliana; Spencer, Charles; Rider, Lisa; Huber, Adam
Abstract Background Juvenile dermatomyositis (JDM) is the most common form of the idiopathic inflammatory myopathies in children. A subset of children have the rash of JDM without significant weakness, and the optimal treatments for these children are unknown. The goal of this study was to describe the development of consensus clinical treatment plans (CTPs) for children with JDM who have active skin rashes, without significant muscle involvement, referred to as skin predominant JDM in this manuscript. Methods The Children's Arthritis and Rheumatology Research Alliance (CARRA) is a North American consortium of pediatric rheumatology health care providers. CARRA members collaborated to determine consensus on typical treatments for JDM patients with skin findings without significant weakness, to develop CTPs for this subgroup of patients. We used a combination of Delphi surveys and nominal group consensus meetings to develop these CTPs. Results Consensus was reached on patient characteristics and outcome assessment, and CTPs were developed and finalized for patients with skin predominant JDM. Treatment option A included hydroxychloroquine alone, Treatment option B included hydroxychloroquine and methotrexate, and Treatment option C included hydroxychloroquine, methotrexate and corticosteroids. Conclusions Three CTPs were developed for use in children with skin predominant JDM, which reflect typical treatment approaches. These are not considered to be specific recommendations or standard of care. Using the CARRA network and prospective data collection, we will be able to apply statistical methods in the future to allow comparisons of JDM patients following these consensus treatment plans.